Advantages to Disadvantages of Cloud Computing for Small-Sized Business - Abdalla, Peshraw Ahmed; Varol, Asaf (Ieee, 2019)
This paper presents a complete overview of the storage landscape and cloud computing. It explains the major advantages and disadvantages of storing data online using cloud storage, how this works, and the basic concepts involved in cloud computing, while also demonstrating the layers of its architecture with reference to the Infrastructure as a Service (IaaS) that contains the cloud storage architecture. The paper further discusses the concept of Storage as a Service (StaaS), which lets users or clients utilize cloud storage to save data by providing them space without them having to use physical storage.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Cloud Storage; Cloud Computing; IaaS; PaaS; iPaaS; SaaS